2022
DOI: 10.1002/sstr.202100185
|View full text |Cite
|
Sign up to set email alerts
|

Atomic‐Level Metal Electrodeposition: Synthetic Strategies, Applications, and Catalytic Mechanism in Electrochemical Energy Conversion

Abstract: Electrochemical energy conversion is considered a promising method to alleviate the global energy crisis and environmental issues. By decreasing the length scale to the atomic level, the energy‐related metal electrocatalysts can possess unique catalytic properties, which can maximize their utilization. The electrodeposition technique has gained unprecedented attention for the synthesis of atomic‐level metal catalysts. In this review, the recent progress on the various strategies used to electrodeposit atomic‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 135 publications
0
16
0
Order By: Relevance
“…16,17 High-angle annular dark-field (HAADF) imaging was used to detect the heavy atoms (Co, Mn, Ni, Ti, and Zr) as the contrast of the atom is proportional to its Z 1.7 (Z for the atomic number) in the HAADF mode of aberration-corrected scanning transmission electron microscopy (STEM). 18,19 Figure 2 illustrates that the bulk structure of the material is well defined and layer-like, but the surface structures are disordered. Heavy atoms are found in both the TM layers and the Li layers near the surface although no heavy atoms can be observed in the Li layers in the bulk of the material.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 High-angle annular dark-field (HAADF) imaging was used to detect the heavy atoms (Co, Mn, Ni, Ti, and Zr) as the contrast of the atom is proportional to its Z 1.7 (Z for the atomic number) in the HAADF mode of aberration-corrected scanning transmission electron microscopy (STEM). 18,19 Figure 2 illustrates that the bulk structure of the material is well defined and layer-like, but the surface structures are disordered. Heavy atoms are found in both the TM layers and the Li layers near the surface although no heavy atoms can be observed in the Li layers in the bulk of the material.…”
Section: Resultsmentioning
confidence: 99%
“…Electrodeposition has become a common method for the synthesis of metal elements, but it is not easy to control the thickness and quantity of shells. Therefore, UPD is widely used as a more “intelligent” surface-limited electrodeposition method [ 59 ]. UPD is an excellent method for the preparation of core–shell structures, especially for the preparation of core–shell nanomaterials with ultra-thin shells or even monolayer shells.…”
Section: Factors Affecting the Orr Performances Of The Core-shell Str...mentioning
confidence: 99%
“…The nucleation rate is mainly affected by the overpotential. 13 According to the related research on the electrocrystallization behavior of indium reported by domestic and foreign scholars, most of the discoveries were made to study the electrochemical behavior of indium alone. Pettit et al 14 studied that the adsorption kinetics of In on Mo was three-dimensional progressive nucleation by chronopotentiometry.…”
Section: Introductionmentioning
confidence: 99%